USING A DOUBLE-COUNT AERIAL SURVEY TO ESTIMATE MOOSE ABUNDANCE IN MAINE - Kantar, Lee E.; Cumberland, Rod E. (Lakehead University, 2013)
Management goals and objectives for moose (Alces alces) in Maine are centered on providing hunting and wildlife viewing opportunity. Robust population estimates of moose are critical to assure that harvest rates are appropriate and biologically sustainable while also addressing values of other user groups. The Maine Department of Inland Fisheries and Wildlife most recently used the relationship between moose sightings by deer hunters and moose abundance to produce density indices within Wildlife Management Districts (WMD). Due to the marked decline of deer hunters in much of northern Maine that invalidates use of this technique, we tested a double-count aerial survey method to estimate moose abundance in 9 northern WMDs. Density estimates ranged from 0.4–4.0 moose/km2, sightability was high (>70%) for all size moose groups (1–≥3 moose), and moose were well distributed across the landscape in early winter. The density estimates tracked closely with trends in moose sighting rate by moose hunters, harvest level, and hunter success rate in the survey area, and were consistent with jurisdictions in eastern Canada that also have low levels of predation and a preponderance of younger-aged forests. The double-count aerial survey is considered the preferred method to estimate population density, whereas hunter sighting indices would be most useful to track temporal population changes within a WMD.